Transcriptome and Metabolome Analysis of the Leaf Colour Mutation Mechanism in a Light-Green Leaf Mutant of Maize - Dan Li; Kuangzheng Qu; Dianrong Ma; Zhenxing Zhu; Xiaochun Lu (Agronomy)
Leaf colour is a valuable morphological phenotype for studying plant metabolism and physiology. To elucidate the mutation mechanism of leaf colour variation in maize, we compared the ethyl methylsulfonate (EMS)-induced maize mutant zmpgl, which has light green leaves, with the wild-type maize line B73. At the seedling stage, the zmpgl mutant presented distinct light green leaf colouration. Comprehensive analyses revealed that both the photosynthetic parameters and pigment contents of the mutant seedlings were significantly lower than those of the wild-type seedlings. Transmission electron microscopy of the mutant leaves revealed alterations in the chloroplast structure, which consequently impaired the photosynthetic efficiency and accumulation of organic matter. Through integrated transcriptomic and metabolomic profiling, we identified differentially expressed genes (DEGs) and differentially abundant metabolites associated with the zmpgl phenotype. These molecular components were associated with pathways related to plant metabolism, chloroplast structure-associated hormone signalling, and redox homeostasis. Further investigation revealed a significant differential expression of genes involved in several critical biological processes, including tetrapyrrole synthesis, lipid metabolism (related to leaf photosynthesis), amino acid metabolism (associated with chlorophyll synthesis and the light response), and abscisic acid (ABA) biosynthesis. These processes are crucial for plant photosynthesis, respiration, and catalytic functions. This study not only provides a valuable resource for further investigation of plant photosynthetic systems but also establishes a foundational framework for the comprehensive functional characterisation of genes involved in the leaf colour change in the zmpgl mutant. These findings contribute to our understanding of the molecular basis of leaf colour variation and its impact on photosynthetic performance in maize.